Pentingnya Kinerja Dilihat dari Faktor Knowledge Characteristic, Meaningful Work dan Kepuasan Kerja Perawat RS An-Nisa Tangerang - Claudia Tari Rumondang (The Asia Pacific Journal Of Management Studies, 2022)
Good quality of health services is reflected in the performance of health services in health facilities, one of which is a hospital. Nurses are health workers with a number that dominates in a hospital, therefore the performance of nurses is one of the factors that affect the quality of health services in a hospital. Nurse performance is related to many factors, including knowledge characteristic, meaningful work and job satisfaction. This study aims to determine the effect of knowledge characteristic and meaningful work on job satisfaction and nurse performance. The research subjects were 204 nurses who worked at An-Nisa Hospital Tangerang. The research uses a quantitative approach with the PLS-SEM method. The results showed that knowledge characteristic and meaningful work had a positive effect on job satisfaction, and knowledge characteristic, meaningful work and job satisfaction had a positive effect on nurse performance.